2018
DOI: 10.3989/gya.0341181
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del secado al aire y solar sobre la calidad nutricional del aceite, las semillas y pieles de las uvas Muscat Hamburg

Abstract: Grape pomace is an agro-industrial by-product from the production of must (grape juice) by pressing whole grapes. In order to evaluate the seeds and skins of the grape pomace, it must first be dried and then separated in a screen machine. The drying of pomace is an important and necessary process for the optimum separation of seeds. The main purpose of this study was to determine the optimum drying process for obtaining high-quality grape seed oil. In this research, open air and solar energy drying methods wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The studies confirm that the fatty acids composition of grape byproducts differs depending on the processing method, the oil contents of grape juice byproducts being lower than of the wine byproducts (Gülcü et al, 2019). Taşeri et al (2018) showed that the drying method significantly affected (p < .05) the free fatty acid contents of seeds, which depend on the lipase activity, the open air method providing better results.…”
Section: Grape Byproducts Chemical Compositionsupporting
confidence: 53%
See 4 more Smart Citations
“…The studies confirm that the fatty acids composition of grape byproducts differs depending on the processing method, the oil contents of grape juice byproducts being lower than of the wine byproducts (Gülcü et al, 2019). Taşeri et al (2018) showed that the drying method significantly affected (p < .05) the free fatty acid contents of seeds, which depend on the lipase activity, the open air method providing better results.…”
Section: Grape Byproducts Chemical Compositionsupporting
confidence: 53%
“…Gülcü et al (2019) reported that the principal sugars of grape juice and wine byproducts are fructose and glucose, whereas saccharose can be found only in seeds. According to the results reported by Taşeri et al (2018), the drying method significantly affects (p < .05) the sugar content of grape peels, the open air solution being better than a solar collector. Mendes et al (2013) analyzed white grape peels and showed that the main neutral sugars were rhamnose, fucose, arabinose, xylose, mannose, galactose, and glucose.…”
Section: Grape Byproducts Chemical Compositionmentioning
confidence: 96%
See 3 more Smart Citations